Die invloed van modellering, gedragsrepetisie en videoband-terugkoppeling op selfopenbaring - Janecke, Benjamin Stephan (University of the Free State, 1979)
Abstract not available
Keywords: Video tapes in psychology; Mental health; Self actualization (Psychology); Behavior modification; Dissertation (M.A. (Psychology))--University of the Free State, 1979